2014
DOI: 10.1038/eye.2014.280
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective contralateral study comparing Descemet membrane endothelial keratoplasty with Descemet stripping automated endothelial keratoplasty

Abstract: Purpose In this retrospective study, the visual outcomes and postoperative complications after Descemet stripping automated endothelial keratoplasty (DSAEK) and Descemet membrane endothelial keratoplasty (DMEK) in the fellow eye were compared. The patient's satisfaction was evaluated. Methods A retrospective analysis of 10 patients, who underwent DSAEK in one eye and DMEK surgery in their fellow eye, was performed. Intraoperative and postoperative complications were recorded. Visual and refractive outcomes wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
54
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(62 citation statements)
references
References 34 publications
3
54
1
1
Order By: Relevance
“…91 This hypothesis was supported by Maier et al, who compared 10 patients who had received DMEK in one eye and DSAEK in the other. 75 Both BCVA and contrast sensitivity were significantly better in the DMEK eyes, but this was not explained by any significant difference in LOAs or HOAs between the two techniques, thus implicating other factors. 75 Several other studies have found correlation between corneal haze and visual acuity following EK, and these will be discussed in section 5.…”
Section: High Order Aberrations and Light Scattermentioning
confidence: 79%
See 1 more Smart Citation
“…91 This hypothesis was supported by Maier et al, who compared 10 patients who had received DMEK in one eye and DSAEK in the other. 75 Both BCVA and contrast sensitivity were significantly better in the DMEK eyes, but this was not explained by any significant difference in LOAs or HOAs between the two techniques, thus implicating other factors. 75 Several other studies have found correlation between corneal haze and visual acuity following EK, and these will be discussed in section 5.…”
Section: High Order Aberrations and Light Scattermentioning
confidence: 79%
“…13 In similar studies of patient-reported outcome measures (PROMS) looking at patients receiving DSAEK in one eye and DMEK in the other, patient satisfaction was high for both techniques; an overall preference was expressed for DMEK -a finding attributed to faster recovery, better UCVA and BCVA, and improved contrast sensitivity. 42,44,75 A confounding factor in contralateral eye patient satisfaction studies is that the more affected eye tends to be the first eye to receive a graft, and in turn tends to be managed with the older surgical technique. This exposes the data to a risk of bias.…”
Section: The Importance Of the Patient Experiencementioning
confidence: 99%
“…Nevertheless, the DMEK procedure seems superior to the DSEK procedure in terms of visual acuity and refractive results. [1][2][3][4] Rebubbling, an additional intracameral air injection to fix graft detachment, is the most frequently required postoperative intervention. 5 The rate of graft detachment in DSEK is low, whereas it is higher in DMEK (10%-63%).…”
mentioning
confidence: 99%
“…5 The rate of graft detachment in DSEK is low, whereas it is higher in DMEK (10%-63%). [1][2][3][4][6][7][8][9] Although the treatment regimen of graft detachment after DMEK varies among surgeons, the higher rate of graft detachment and the consequent higher intervention rate postoperatively could be considered as disadvantages of DMEK surgery compared with DSEK surgery. 1,[10][11][12] The higher rebubbling rate after DMEK seems to have no effect on the visual outcome and the postoperative development of endothelial cell density, but additional interventions are associated with more effort for the patient and the treating facility and with a potentially increased risk of infection for the patient.…”
mentioning
confidence: 99%
“…Recently, a few retrospective studies comparing visual outcomes after DMEK and DSAEK were published. [8][9][10][11] In 3 of these studies, comparability was given by either comparing the course of fellow eyes [9][10][11] or matching with respect to diagnosis and donor characteristics. 8 With regard to visual acuity as the primary outcome measure in the present study, we compared visual rehabilitation after DMEK versus DSAEK based on the course of pairs of eyes with identical baseline visual acuity.…”
mentioning
confidence: 99%